2004
DOI: 10.1023/b:ddas.0000034548.89117.d6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Esophageal Mucosal Levels of Vitamin C: Role in the Pathogenesis and Neoplastic Progression of Barrett's Esophagus

Abstract: Antioxidants may protect against the development of esophageal adenocarcinoma. Blood samples and endoscopic biopsies (squamous, Barrett's, and gastric mucosa) were obtained from 48 Barrett's esophagus (BE) patients, while 48 age- and sex-matched controls provided blood samples only. Plasma concentrations of vitamins A, C, and E were measured in all subjects, while vitamin C was measured in relation to the type of mucosa. Plasma total vitamin C level, but not vitamin A or E, was lower in BE patients compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Plasma and tissue vitamin C levels, but not vitamin E levels, were decreased in Barrett's esophagus compared with normal squamous epithelium [19]. Although not all enzymes involved in detoxification of radicals are decreased in Barrett's esophagus and adenocarcinoma, overall scavenging capacity seems diminished during esophageal carcinogenesis.…”
Section: Inflammation and Oxidative Stressmentioning
confidence: 85%
“…Plasma and tissue vitamin C levels, but not vitamin E levels, were decreased in Barrett's esophagus compared with normal squamous epithelium [19]. Although not all enzymes involved in detoxification of radicals are decreased in Barrett's esophagus and adenocarcinoma, overall scavenging capacity seems diminished during esophageal carcinogenesis.…”
Section: Inflammation and Oxidative Stressmentioning
confidence: 85%
“…Fruit and vegetables are high in anti-oxidants, especially in vitamin C, dietary intake of which is reduced in oesophageal adenocarcinoma patients [38,[67][68][69][70] . Tissue levels of vitamin C are also lower in areas of specialised intestinal metaplasia than in squamous mucosa suggesting that oxidative stress may be implicated in the neoplastic progression of Barrett's oesophagus [71] . Reflux of gastric contents into the oesophagus can enhance the production of free radicals which may cause damage to lipids, proteins and DNA through oxidative stress and may be implicated in the development of Barrett's oesophagus and/or oesophageal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effect of antioxidants may also reduce hydroperoxides in esophageal epithelium, which can otherwise activate lipoxygenase and cyclooxygenase, leading to the production of inflammatory prostaglandins and leukotrienes, an important step in the inflammatory process (54,55). The potential importance of antioxidant defenses against excessive freeradical production in the esophageal epithelium can be gathered from studies that have found lower levels of plasma and mucosal vitamin C in the metaplastic epithelium of Barrett's esophagus samples (56) and complete loss of glutathione peroxidase-3 expression, an antioxidative selenoenzyme, in EA tumors (57). Smoking, another source of oxidative damage, has been associated with a twofold increased risk of EA (58).…”
Section: Discussionmentioning
confidence: 99%